The Impact of Educational Games at Professional English Lessons in Iraqi Schools - Abdalbaqi, Dalal Fanar (Journal of Tikrit University for Humanities, 2024)
The purpose of this study we present the most helpful material in the field of teaching foreign languages is to analyze the results of using professional English courses with educational games in Iraqi schools, indicates, it’s a tools used in the teaching second language. In this work, we aim to explore the effects of education games on improving and developing learners’ . The participants are fifth grade from two different elementary schools. This is a deliberate selection on the part of the researcher. One hundred and thirty-eight students were selected randomly from the fifth grade class. After testing the tool with two groups; experimental and control group, researchers concluded that educational games are more beneficial than more conventional methods. Playing educational games significantly affects the motivation of Iraqi students, according to the results of this study, and they are also helpful in increasing students' exposure to vocabulary and providing students with meaningful practice of language.